2015
DOI: 10.1089/acm.2014.0152
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Laughter Therapy on Mood State and Self-Esteem in Cancer Patients Undergoing Radiation Therapy: A Randomized Controlled Trial

Abstract: These results indicate that laughter therapy can improve mood state and self-esteem and can be a beneficial, noninvasive intervention for patients with cancer in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 18 publications
2
17
0
6
Order By: Relevance
“…First, our study showed the positive impact of a group intervention combining self-care and self-hypnosis on selfesteem and emotional distress. This is in line with other studies showing the impact of psychological interventions [26][27][28][29] and hypnosis [29,35,36] on these variables. Our intervention also allowed positive change in emotion regulation strategies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…First, our study showed the positive impact of a group intervention combining self-care and self-hypnosis on selfesteem and emotional distress. This is in line with other studies showing the impact of psychological interventions [26][27][28][29] and hypnosis [29,35,36] on these variables. Our intervention also allowed positive change in emotion regulation strategies.…”
Section: Discussionsupporting
confidence: 93%
“…Some psychological interventions have been tested to improve self-esteem and emotional distress of cancer patients [26][27][28][29]. In oncology settings, there is a growing interest in alternative methods in order to manage treatment side effects in a non-pharmacological way.…”
Section: Introductionmentioning
confidence: 99%
“…Humor seemed to help develop a sense of normalcy of everyday challenges, despite the physical and cognitive limitations. While the impact of humor and laughter in various disease states has previously been documented (Ghodsbin, Ahmadi, Jahanbin, & Sharif, ; Kim et al, ; Merz et al, ), our study provides initial evidence on the effect of humor in stroke recovery.…”
Section: Discussionsupporting
confidence: 57%
“…Humor jest też zalecany pracownikom oddziałów onkologicznych dla ich ochrony przed stresem [29]. Wiele obserwacji wskazuje na korzystne działanie humoru u chorych na nowotwory [30][31][32], a czynione były nawet próby zastosowania humoru jako terapii wspomagającej odporność u chorych na nowotwory [33].…”
Section: Leczniczy Wpływ Humoru W Poszczególnych Chorobachunclassified